Metode dan Pendekatan dalam Studi Islam: Pembacaan atas Pemikiran Charles J. Adams - Zuhriyah, Luluk Fikri (Program Pascasarjana UIN Sunan Ampel Surabaya, 2007)
Islam has been an interesting object of study for both Muslims and non-Muslims over a long period of time. A number of methods and approaches have also been introduced. In due time, Islam is now no longer understood solely as a doctrine or a set of belief system. Nor is it interpreted merely as an historical process. Islam is a social system comprising of a complex web of human experience. Islam does not only consist of formal codes that individuals should look at and obey. It also contains some cultural, political and economic values. Islam is a civilization. Given the complex nature of Islam it is no longer possible to deal with it from a single point of view. An inter-disciplinary perspective is required.In the West, social and humanities sciences have long been introduced in the study of religion; studies that put a stronger emphasis on what we currently know as the history of religion, psychology of religion, sociology of religion and so on. This kind of approach in turn, is also applied in the Western studies of the Eastern religions and communities.Islam as a religion is also dealt with in this way in the West. It is treated as part of the oriental culture to the extent thatâas Muhammad Abdul Raouf has correctly arguedâIslamic studies became identical to the oriental studies. By all means, the West preceded the Muslims in studying Islam from modern perspectives; perspective that puts more emphasis on social, cultural, behavioral, political and economic aspects. Among the Western scholars that approach Islam from this angle is Charles Joseph Adams whose thought this research is interested to explore.